Teachers as intellectuals: Their strata and their main function as interpreter and translator - Ruiz Mendoza, Karla Karina (IE Revista de Investigación Educativa de la REDIECH, 2024)
In a presidential term in which the concept of the intellectual was revisited in Mexico, this essay aims to present the multifaceted role of teachers in the current educational context, highlighting them as rural intellectuals, whose primary function is as interpreters and translators of knowledge. Drawing from authors such as Gramsci, Dubet, and Ball, it examines how teachers emerge as organic intellectuals in response to the needs of their social and economic context. The micropolitics within educational institutions and the diversification of school types, teaching modalities, and contextual and technological changes have complicated the identification of teachers as active agents. Additionally, the advent of generative artificial intelligence presents new challenges and opportunities, requiring critical skills to evaluate and contextualize the generated information. Therefore, the functions of teachers are emphasized: emotional, investigative, knowledge transmission, organizational, and union roles. Through a critical analysis of educational policies and policy technologies, it is concluded that teachers must assume an active role in interpreting and adapting educational policies and content to prepare students to contribute significantly to society.